Kapasitas Penyerapan dan Penyimpanan Air pada Berbagai Ukuran Gel dari Tepung Karaginan untuk Pembuatan Media Tanam Jeloponik - Hakim, Muhammad Faisol; Setiari, Nintya; Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
There is a trend in using gel for hydrophonic. We examine the potency of water absortion and holding capacity from different size of carrageenan gel. This research was conducted from may to july 2006. the size of gel, i.e.: 1 cm3, 2 cm3, 3 cm3 and in powder form were used as independent variables. Where as, water absorbtion and holding capacity act as dependent variables. Collected data were analized by ANOVA. Result indicated that gel size significantly effect water absorbtion and holding capacity. In powder form, water absorbtion and holding capacity is the most optimal, but the gel was easily destroyed. Therefore, the best size if gel that should be used for hydrophonic were 2 cm3 and 3 cm3.